engaruh Kualitas Produk, Kualitas Pelayanan, Emosional, Harga, Dan Biaya Terdahadap Kepuasan Konsumen Sayuran Organik Ceritanik - Fazriah, Shofa; Wulandari, Yeni Sari; Mariyani, Siti (Peneliti.net, 2025)
Consumer satisfaction is a feeling of pleasure or disappointment from a person as a result of a comparison between the perceived and expected performance of the product. This study aims to determine the simultaneous and partial effects of product quality, service quality, emotional, price, and cost on customer satisfaction. The population in this study were consumers who had bought Ceritanik organic vegetables at least 2 times with a sample of 67 respondents. The method used in this research is descriptive quantitative and multiple linear regression analysis. The results of this study simultaneously show that all variables have an effect on Ceritanik's customer satisfaction as indicated by a significance value of 0.000.Partially it is known that product quality affects customer satisfaction with a Sig. value of 0.015. Service quality affects customer satisfaction with a Sig. value of 0.245. Emotional customers affect customer satisfaction with a Sig. value of 0.027. Product price affects customer satisfaction with a Sig. value of 0.000, and cost affects customer satisfaction with a Sig. value of 0.797.